Innovative linguistic ideas and concepts of Larysa Shevchenko - Styshov, Oleksandr; Syzonov, Dmytro (Current issues of Ukrainian linguistics: theory and practice, 2019)
The article establishes innovative views on modern linguistics in systematic analysis of numerous works by prof. L.I. Shevchenko – a prominent Ukrainian linguist, head of the department of stylistics and language communication, a vice-chairman of the Ukrainian committee of slavists, a member of two commissions of the International committee of slavists (media linguistic and stylistic), chief editor of the international edition «Actual issues of Ukrainian linguistics: theory and practice». The pre-anniversary article focuses on the scholar’s concept of intellectualization of the Ukrainian literary language, integration of the researcher’s works with European academic discourse, particularly, in the context of innovative linguistic directions – legal linguistics, media linguistics, business linguistics, political linguistics etc., the analysis of which is determined by exploratory vector of a modern linguist. The authors also mention the works of prof. L.I. Shevchenko’s mentees. More than 10 PhD and doctoral theses have been defended under the scholar’s supervision. Prof. L.I. Shevchenko holds a special place at Kyiv stylistic school, which is confirmed by the researcher’s numerous works that have qualitatively changed and deepened views on some issues of theoretical and functional stylistics. These are primarily theoretical problems of modern linguistics and the search for new research paradigms, the problems of stylistic differentiation of the Ukrainian literary language, the analysis of concepts of the theory of language intellectualization, modern view on idiostylistics, the issue of the national language status in contemporary social space, a profound analysis of Ukrainian linguistics in ideas, concepts and personalities. Productivity and polyphony of the researcher’s interests, her wide scientific outlook, encyclopedic knowledge, desire to be modern in the context of innovative views and ideas in world linguistics, fundamental role in formation of new research directions define a significant place of prof. L.I. Shevchenko in the XXI century linguistics.
Keywords: L.I. Shevchenko, Kyiv stylistic school, linguistic tradition, neolinguistics, Kyiv University.